IMPROVING THE REGULATION OF THE STOCK MARKET IN THE NATIONAL ECONOMY - Sultanov Sherali Nuralievich (European Science Publishing, 2024)
The main component of the financial market is the stock market. The stock market is a sphere of securities issuance and trading, and a set of financial relations in the circulation of securities. Its main task is to launch the "savings-investment" mechanism, extended repetition It consists of collecting and distributing financial resources necessary for production and technical development, attracting investments of legal and physical persons, increasing it further and ensuring the modernization of the economy by directing it to economic sectors. Also, the stock market and the intermediaries operating in it are a component of the financial system and provide an opportunity to accelerate the process of redistribution of excess funds from investors to consumers. In the stock market, on the one hand, there are capital suppliers, individuals with free funds, legal and natural persons who wish to invest and increase these funds, as well as the state as a separate entity. is enough. On the other hand, there are market entities that need initial or additional capital necessary for starting new production, providing works, services, or modernizing, expanding, and renovating production. It should be noted that enterprises, organizations, residents, as well as the state can directly participate as applicants for capital.